2015
DOI: 10.3109/09513590.2015.1017812
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technique of endometrioma excision impacts on the ovarian reserve. Single-port access laparoscopy versus multiport access laparoscopy: a case control study

Abstract: Several recent studies report the detrimental effect of endometrioma excision on the ovarian reserve. Surgical technique and the excessive use of bipolar coagulation could be the key factors. Single-port access laparoscopy (SPAL) ovarian cystectomy has been reported as a comparable procedure to conventional laparoscopy in terms of operative outcomes. The aim of this study was to evaluate whether the single-port surgery affects the ovarian reserve whilst performing laparoscopic ovarian cystectomy for unilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…In contrast, Vignali et al reported that the postoperative decrease in AMH levels in women who had undergone laparoscopic excision of ovarian endometrial cysts was temporary; AMH levels returned to preoperative values 12 months after surgery [ 37 ]. Angioni et al investigated the feasibility of single-port access laparoscopy (SPAL) compared with multiport laparoscopy (MPL) for cystectomy of ovarian endometriomas [ 38 ]. Over a 3-month follow-up period, they observed a significant decrease in AMH serum concentrations and antral follicle count after SPAL compared with MPL and concluded that SPAL cystectomy should not be recommended for women with endometriomas who desire pregnancy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Vignali et al reported that the postoperative decrease in AMH levels in women who had undergone laparoscopic excision of ovarian endometrial cysts was temporary; AMH levels returned to preoperative values 12 months after surgery [ 37 ]. Angioni et al investigated the feasibility of single-port access laparoscopy (SPAL) compared with multiport laparoscopy (MPL) for cystectomy of ovarian endometriomas [ 38 ]. Over a 3-month follow-up period, they observed a significant decrease in AMH serum concentrations and antral follicle count after SPAL compared with MPL and concluded that SPAL cystectomy should not be recommended for women with endometriomas who desire pregnancy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of these 13 studies, including four RCTs9–12 and nine retrospective studies,13–21 are shown in tables 1 and 2. The geographic distribution of these study institution was varied, with seven reports from Korea, two from Italy and one from America, England, China and Turkey, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All studies9–21 reported operative time for 1542 patients, and the LESS group had longer operative time than the CL group (WMD: 3.43 min; 95% CI: −0.03 to 6.88; p=0.05). Significant heterogeneity was found between these studies (χ²=34.85, df=12, p<0.001; I²=66%)(figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the removal of ovarian endometriosis is one of the fields in which the outcome of conventional LESS surgery is reported to be inferior to multiport laparoscopy (in terms of residual ovarian reserve), likely because in LESS surgery electrocautery is likely to be used instead of suturing to achieve hemostasis. 178,179 In this perspective, one could claim that overcoming the extreme ergonomic challenges of LESS surgery by robotic assistance makes sense also for this application. Gargiulo et al have recently described a technique of RSS excision of endometrioma that includes a modification of the partial stripping and partial CO 2 laser ablation originally proposed by Donnez et al 83,180 In conclusion, RSS surgery has made some significant strides in recent years, in parallel with the development of the first generation of dedicated technology.…”
Section: Single-site and Natural Orifice Robotic Surgerymentioning
confidence: 99%